Relación entre síndrome bronco-obstructivo y lactancia materna en niños menores de 3 años en el Hospital Isidro Ayora de Loja, durante el periodo febrero - agosto 2016 - Lalangui Castillo, María Carolina (2016)
Acute respiratory infections (ARI) are a worldwide health issue of significant priority. Most deaths occur before turning one year old, with bronchial obstructive syndrome (BOS) and pneumonia being among the most prominent cases. The prevalence of bronchial obstruction in infants and toddlers below the age of 3 years is 50%. Human milk is undoubtedly the best, it offers many advantages, such as immunological defences which are well known in the first 6 months of life. General objective was: To determine the relationship between bronchial obstructive syndrome and breastfeeding in children under 3 years old in the hospital 'Isidro Ayora de Loja' during the period from February to August It was a qualitative and quantitative study of a descriptive, observational and cross-sectional cohort nature. The investigation studied 130 patients who met the inclusion criteria. The instrument used was the survey which obtained the following results: The time of exclusive breastfeeding in the patients studied was up to 6 months of age with 70.8%, 26.9% of these same patients had mild bronchospasm while 33.3% suffered from recurrent bronchospasm, thus breast milk is considered to be a protective factor. However, from 7 to 12 months old, the first episodes of bronchial obstructive syndrome started to show in 53.8% and on a recurring basis in 61.1%. Bronchial obstructive syndrome is predominant within male patients with 57.7%, the most associtated cause was moisture in housing with 62.3%, patients younger than 12 months of age were the most affected with 54% and 70% of them live in urban areas. Keywords: Bronchial obstructive syndrome; breastfeeding, children.